OPTIMALISASI LITERASI DIGITAL DALAM MENINGKATKAN KESADARAN KEAMANAN SIBER UNTUK SISWA DI SMK KESEHATAN CIPTA BHAKTI HUSADA YOGYAKARTA - Siregar, Ilham Ramadan Pandu Setia Negara; Hidayat, Rahmat Rian; Candraningtyas, Anindya Dewi; Hissan, Iin Khaeratun; Oktaviani, Ria (Jurnal Pengabdian Masyarakat Nasional, 2024)
Digital literacy is not only limited to the ability to use digital devices and applications, but also involves a deep understanding of cyber security awareness. In this digital era, threats to cyber security are increasingly complex and can affect the continuity of every aspect of life, including education and health. Therefore, increasing awareness of the importance of cyber security, especially among students at the Cipta Bhakti Husada Yogyakarta Health Vocational School is crucial. In this research, the author used a qualitative research method with a descriptive model. Through this activity, it is hoped that it can provide students with a better understanding of potential risks and precautions in cyberspace. In addition, we want to improve students' skills in using technology wisely, ethically, and safely. We also need to be committed to continuing to develop digital literacy and cyber security awareness among students so that students can grow into an intelligent and creative generation in facing a digital era full of challenges. In this way, they can become agents of change who are able to face the challenges of the digital world with a positive and responsible attitude. Keywords: Digital Literacy; Cyber Security Cipta Bhakti Husada Yogyakarta Health Vocational School Students